2020
DOI: 10.4103/jfmpc.jfmpc_207_20
|View full text |Cite
|
Sign up to set email alerts
|

A study of contralateral occult inguinal hernia in adult male patients undergoing total extraperitoneal herniorraphy

Abstract: Background: The incidence of contralateral occult hernia (COH) varies from 4.2% to 57.5%. Total extraperitoneal (TEP) gives us opportunity to visualize contralateral groin for occult hernia and its simultaneous repair. Ultrasonography (USG) helps to diagnose occult hernia preoperatively with detection rate of 96.6% with specificity 84.4%. Objective: The aims of this study were to identify the incidence of contralateral occult inguinal hernia in clinically diagnosed unil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…In one study [ 17 ] follow-up duration was not reported. In a further study [ 19 ] zero events were reported in both study arms, preventing synthesis. Five studies [ 16 , 17 , 21 23 ] contributed to an effect direction plot for this outcome (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In one study [ 17 ] follow-up duration was not reported. In a further study [ 19 ] zero events were reported in both study arms, preventing synthesis. Five studies [ 16 , 17 , 21 23 ] contributed to an effect direction plot for this outcome (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Upon full-text examination, only 26 of these articles contained data comparing technique outcomes. A further 18 articles from this group were excluded due to contamination with recurrent hernia repairs, prophylactic repairs, or an excluded TEP methodology, leaving 8 articles [ 3 , 4 , 16 , 17 , 19 , 21 23 ], with a total of 18,153 patients, included in the final analysis.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations